2012
DOI: 10.4103/2230-8210.102986
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia in type 2 diabetes: Standpoint of an experts′ committee (India hypoglycemia study group)

Abstract: The epidemic of type 2 diabetes and the recognition that achieving specific glycemic goals can substantially reduce morbidity have made the effective treatment of hyperglycemia a top priority. Despite compelling evidence that tight glycemic control is crucial for delaying disease progression, increased risk of hypoglycemia associated with such control underscore the complexity of diabetes management. In most cases, hypoglycemia results from an excess of insulin, either absolute or relative to the available glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In India, which has the second largest number of diabetes patients, there is negligible data on the epidemiology of hypoglycemia. [ 15 ] The limitation of the study is that the knowledge is assessed among patients attending a diabetes free Clinic in a Medical College Hospital and may not be accurately representing that in a community comprising both affordable and poor patients.…”
Section: Discussionmentioning
confidence: 99%
“…In India, which has the second largest number of diabetes patients, there is negligible data on the epidemiology of hypoglycemia. [ 15 ] The limitation of the study is that the knowledge is assessed among patients attending a diabetes free Clinic in a Medical College Hospital and may not be accurately representing that in a community comprising both affordable and poor patients.…”
Section: Discussionmentioning
confidence: 99%
“…[9] The list of common symptoms of hypoglycemia was made by wide literature search. [710121314] The patients were enquired whether they had any of the listed hypoglycemic symptoms in the past 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…[8] The India Hypoglycemia Study Group highlights that there is negligible data on the epidemiology of hypoglycemia in type 2 diabetes from India, which has the second largest number of diabetes patients in the world. [9] The ADA workgroup on hypoglycemia has reported a condition, “Probable Symptomatic Hypoglycemia” where there are typical symptoms of hypoglycemia without a measured plasma glucose concentration. According to them, even though these conditions may not be suitable outcome measures for clinical studies evaluating therapy, it would be useful to report such episodes.…”
Section: Introductionmentioning
confidence: 99%
“…Disabling and life threatening micro and macrovascular complications of diabetes highlights the need for optimum management [ 2 ]. Benefits of intensive glycaemic control in prevention of these complications are well recognized [ 3 , 4 ]. However it has been observed that most patients do not reach the optimum level of glycaemic control despite well defined management protocols [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of intensive glycaemic control in prevention of these complications are well recognized [ 3 , 4 ]. However it has been observed that most patients do not reach the optimum level of glycaemic control despite well defined management protocols [ 4 ]. This, at least partly, is attributable to the fear of hypoglycaemia, both among patients and treating medical professionals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%